The Role of Self-Regulated Learning and Student Engagement in Academic Activities towards Math Achievement - Salma, Nabila; Alsa, Asmadi (Universitas Muhammadiyah Yogyakarta, 2023)
This research aims to empirically examine the role of self-regulated learning and student engagement in academic activities in math achievement. The research design used was a correlational survey. The subjects were students at Madrasah Aliyah Negeri in Yogyakarta. The research sample was selected using a proportional stratified random sampling technique with 96 students. Math achievement was determined from students' daily evaluations, and data were collected using a self-regulated learning scale and a scale of student engagement in academic activities. Data were analyzed using multiple regression analysis. According to the findings, self-regulated learning and student engagement in academic activities significantly predicted math achievement. Both self-regulated learning and student engagement in academic activities positively influenced math achievement. The combined contribution of self-regulated learning and student academic engagement to mathematics achievement was 37.1%. Self-regulated learning contributed more (17.39%) than academic engagement (19.77%) to mathematics achievement. This study recommends that students, teachers, and parents pay attention to self-regulated learning and student engagement factors.